Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/mog.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

New insights in the development of pancreatic cancer

Abstract: Purpose of review The review intends to describe recent studies on the development of pancreatic cancer from a genetic, molecular, and microenvironment perspective. Recent findings Pancreatic cancer has been discovered to have distinct molecular subtypes based on transcriptome analyses that may have implications for treatment. Recent studies are also mapping the complex molecular biology of this cancer as it relates to the core signaling abnormalities inherent to this disease. There have been discoveries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Since we observed axons in close proximity to PanIN epithelial cells and showed that PDAC cells robustly recruited sensory axons, we hypothesized that nerves, like other stromal components (21,25), may communicate with and regulate the PanIN epithelium. The KPC Pdx1 PanIN epithelia were negative for expression of several nerve-responsive elements such as the neurotrophic receptors p75, TrkA, TrkB and TrkC that can be expressed in human PDAC (4) (data not shown).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Since we observed axons in close proximity to PanIN epithelial cells and showed that PDAC cells robustly recruited sensory axons, we hypothesized that nerves, like other stromal components (21,25), may communicate with and regulate the PanIN epithelium. The KPC Pdx1 PanIN epithelia were negative for expression of several nerve-responsive elements such as the neurotrophic receptors p75, TrkA, TrkB and TrkC that can be expressed in human PDAC (4) (data not shown).…”
Section: Resultsmentioning
confidence: 88%
“…Such time- and context-specific roles of oncogenic factors are well described in PanIN and PDAC tumorigenesis (for review see ref. ((25)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we observed axons in close proximity to PanIN epithelial cells and showed that PDAC cells robustly recruited sensory axons, we hypothesized that nerves, like other stromal components (21,25), may communicate with and regulate the PanIN epithelium. The KPC Pdx1 PanIN epithelia were negative for expression of several nerve-responsive elements such as the neurotrophic receptors p75, TrkA, TrkB and TrkC that can be expressed in human PDAC (4) (data not shown).…”
Section: Panin Neuroendocrine Cells Express the Substance P Neuropeptmentioning
confidence: 99%
“…Of note, PDAC is characterised by a hypoxic, immunosuppressive and highly fibrotic environment, with stromal components outnumbering pancreatic cancer cells [23,24]. Intricate communication between pancreatic cancer cells and their surrounding environment, driven by a dynamic signalling network of cellular and matrix remodelling enzymes, cytokines, chemokines and growth factors, collectively promotes tumour growth and treatment resistance [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%